Sikap dan Kepedulian Remaja dalam Penanggulangan Penyalahgunaan Narkoba - Sri Yuni Murtiwidayanti (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
This study aims to comprehend the effect of knowledge on attitude and concern of adolescents in overcoming drugs abuse. It is a correlational research type (correlationalstudies).The location of research is determined purposively under certain considerationsthat the area is vulnerable ofdrugs abuse, as a student city, whereas its society is very heterogeneous and is asa tourism destination.Based on this characteristic condition, thenthe city of Yogyakarta is chosen.The target of the research subject is determined purposively, namely 106 respondents are taken from high-school students (SLTA).The object of the researchtarget is knowledge, attitude and concern of the youngsters inovercoming the drugsabuse.Data are technically collected by using questionnaires, interviews and ob servations. The result of analysis shows that there is a positive influence of teenagers’ knowledgetowards attitude and concern in overcoming of drugs abuse.The knowledge about drugs’ threat contributes effectively as much as 45,140 percent in preventing drugs abuse and some other factors do for the same as much as 54,860 percent.This research recommends several points as follow: 1) the Ministry of SocialAffairs through the Directorate of Social Rehabilitation of Drugs Abuse Victims puts forward the strengthening of human resources especially in youth prevention program of drugs abuse and provides necessary knowledge on drugs threat; 2) the families monitor their children relationship and activities, provide opportunities for their children to study further adequately and that of doing positive activities and also providing affection and attention;3) Communities should be responsive to any possible situations that enable drugs abuse to happen in their environment; 4) School Party needs to set up curriculum (teaching material) on drugs’ threat,to enhance Guidance and Counseling teachers in handling its risk,and to build up strong networking with related and competent parties.